Facebook Social Media: How does it Affect First-Year Students' Description Writing Skills? - Andi Paida; Abdul Wahid; Andi Sukri Syamsuri; Andi Hasrianti; Abdul Rahman Rahim (AL-ISHLAH: Jurnal Pendidikan, 2022)
Facebook is widely claimed to have an important influence on students' writing skills, but studies on its impact on students' descriptive writing skills, especially in the first grade, are still very limited by previous researchers. Because of the scarcity of studies, this study attempts to measure the effect of social media Facebook on the descriptive writing skills of first-year students. 35 students from the Indonesian Language and Literature Education Study Program aged between 16-18 years were involved in this study as research subjects. They were selected after taking the Indonesian Language Competency Test (UKBI) and the range of scores obtained was high (75-79.9%). Non-random sampling was used to select research subjects. This study used a one group pretest-posttest experimental design. The data in this study were obtained from pretest and posttest activities using a descriptive writing skill test instrument. Data analysis was carried out using SPSS for Windows version 25. The results of this study indicate that the average score of students before the Facebook social media intervention was 61.43 and after the intervention, the average score obtained was 83.03. Meanwhile, based on the one-sample t-test, it shows that Facebook has a significant effect on students' description writing skills. The implication of the findings of this study is that Facebook is a social media that can be an ideal and comfortable learning tool that can lead students to develop better descriptive writing skills in higher education.